Day 3 Poly (I:C)-activated dendritic cells generated in CellGro for use in cancer immunotherapy trials are fully comparable to standard Day 5 DCs - Truxova, Iva; Pokorna, Katerina; Kloudova, Kamila; Partlova, Simona; Spisek, Radek; Fucikova, Jitka (Immunology letters, 2014)
BACKGROUND: Dendritic cells (DCs) are professional antigen-presenting cells that are capable of inducing immune responses. DC-based vaccines are normally generated using a standard 5- to 7-day protocol. To shorten the DC-based vaccine production for use in cancer immunotherapy, we have developed a fast DC protocol by comparing standard DCs (Day 5 DCs) and fast DCs (Day 3 DCs). METHODS: We tested the generation of Day 5 versus Day 3 DCs using CellGro media and subsequent activation by two activation stimuli: Poly (I:C) and LPS. We evaluated DC morphology, viability, phagocyte activity, cytokine production and ability to stimulate antigen-specific T cells. RESULTS: Day 5 and Day 3 DCs exhibited similar phagocytic capacity. Poly (I:C)-activated Day 5 DCs expressed higher levels of the costimulatory and surface molecules CD80, CD86 and HLA-DR compared to Poly (I:C)-activated Day 3 DCs. Nevertheless, LPS-activated Day 5 and Day 3 DCs were phenotypically similar. Cytokine production was generally stronger when LPS was used as the maturation stimulus, and there were no significant differences between Day 5 and Day 3 DCs. Importantly, Day 5 and Day 3 DCs were able to generate comparable numbers of antigen-specific CD8(+) T cells. The number of Tregs induced by Day 5 and Day 3 DCs was also comparable. CONCLUSION: We identified monocyte-derived DCs generated in CellGro for 3 days and activated using Poly (I:C) similarly potent in most functional aspects as DCs produced by the standard 5 day protocol. These results provide the rationale for the evaluation of faster protocols for DC generation in clinical trials.
Keywords: Phenotype; Cytokines; Monocyte; Cancer immunotherapy; Dendritic Cells; Neoplasms; dendritické buňky; nádory; antigenní specifita receptorů T-buněk; cytokiny; časové faktory; Cancer Vaccines; Time Factors; Immunotherapy; buněčná diferenciace; lidé; Antigen-Presenting Cells; T-Cell Antigen Receptor Specificity; Immunophenotyping; protinádorové vakcíny; imunofenotypizace; T-lymfocyty - podskupiny; antigen prezentující buňky; imunoterapie; Fast generation; fagocytóza; Phagocytosis; poly I-C; Dendritic cell; Cell Differentiation; buněčné kultury; Cell Survival; fenotyp; Cell Culture Techniques; T-Lymphocyte Subsets; viabilita buněk; Vaccine; Poly I-C; Humans